The pernicious of a not learned lesson - Mendoza Michilot, María (2013)
The so-called “chicha” journal (prensa “chicha” in  Spanish) represents the darkest advertising, informative and sociopolitical phenomenon of Peruvian journalism. It doesn’t have precedent in the sense that it was promote from the top of the political power with a specific purpose, using resources from national exchequer; there are not similar experiences in other democratic systems. To damage, libel or defame the opponents from the State scandalized the international community to the point that the international organizations demanded the respect of the rights of the aggrieved, persecuted and the libeled ones. In this article we analyze, from a historical perspective, the scope of this phenomenon that today gains currency since the ex-president Alberto Fujimori return to the dock to respond his contributors, already condemned for this case, who blame him for being the responsible for thediverting of tens of millions of soles to finance this yellow tabloids. This issue is analyzed in the research called “Historia de los medios de comunicación en el Perú: Siglo XX/ 100 años de periodismo en el Perú/ 1900-1948 y 1949-2000, book of my authorship and edited by “Fondo Editorial de la Universidad de Lima” in two volumes, which we took several passages for this article.